Analysis of foreign experience of implementation of the dual form of education and accessibility of its implementation in Ukraine - Lechachenko, Taras (Technology audit and production reserves, 2019)
The object of research is the foreign experience of the dual form of education. One of the most problematic places is the effective transfer of the dual form of education to countries with a lack of experience in the implementation and functioning of this type of education. The difficulty of transferring dual education lies in the long-term formation of a model in the countries of origin. Characteristic features of dual learning models were obtained as a result of the influence of local factors and conditions of the countries of origin. The complexity of the transfer also lies in the formalization of the assessment data of the potential of the country of implementation. To solve this problem, fuzzy logic methods are best suited. The advantage of using a fuzzy logic apparatus is the ability to formalize the data of complex systems, converting qualitative indicators into quantitative ones and vice versa. Method of fuzzy inference of the Matlab software environment is used. In this paper, an analysis of the prerequisites for the introduction of dual education in Ukraine is carried out. The analysis of the foreign experience of dual education is carried out. As a result, factors are identified and grouped into three subsystems (economic, political, cultural and educational) to assess the potential for introducing dual education in Ukraine. The simulation results shown in the study provide an answer to the question of the feasibility of implementing the dual form of education and assessing this potential of Ukraine. The data obtained as a result of modeling indicate the feasibility of introducing dual education in Ukraine. This is due to the fact that the fuzzy modeling method showed that the integral estimate belongs to the mean of the output term. Among the positive factors that influenced this result, it is worth noting the level of government spending on GDP and the level of prestige of vocational education. The advantage of research is a quantitative assessment of the potential of transfer of the dual form of education in Ukraine, which is also important from the point of view of the international discourse of transfer of the dual form of education. The paper formalizes the model of the country's potential for the introduction of dual education.